The Sudden Awakening / Gradual Cultivation Schema. A Somaesthetic Approach to Jinul’s Thought - Luque-Moya, Gloria (My University, 2020)
The aim of this paper’s presentation is to examine the Sudden Awakening-Gradual Cultivation Schema from a somaesthetic approach to show Jinul’s teachings as an embodied and highly conscious art of living. For that, I start analyzing what Jinul defined as the true Buddha-nature in relation to Richard Shusterman’s definition of soma; that is, an integrative view of body and mind. Then, I consider Jinul’s instruction for gradually cultivation through a comparative methodology that brings these guidelines into dialogue with somaesthetic perspectives. This kind of interchange could help us to understand Jinul’s thought as a way of life concerned with self-improvement. This paper is accomplished by a final reflection on Jinul’s schema as a way of experiencing a meaningful life, as an art of living which connects Buddhism with issues of humanism, aesthetics and ethics.
Keywords: Budismo; Somaesthetics; Buddhism; Jinul